Disease, Healing and Medical Knowledge in an Old Bulgarian Collection of Miracle Stories - Hristov, Yanko M.; Kostadinova, Dafina (Studia Ceranea, 2022)
The Old Bulgarian hagiographical collection of miracle stories, named A Tale of the Iron Cross, is relatively well known among the scholars, but a sufficient number of its details still has not been studied properly. In fact, such a peculiarity seems somehow strange, especially if we take into consideration that the mixture of translated and original strata in the present Tale’s version does not hinder its significance as a valuable primary source of historical information. There can be no doubt that the religious aspect in the hagiographical collection in question is the leading one in the foreground. On the other hand, however, the records of the daily life activities should not be underestimated either. Their presence within the frames of the Tale helps a lot in the scholars’ attempts to reconstruct the knowledge, skills, habits or principles of social behaviour in the Bulgarian society in the late 9th – early 10th century.